2018
DOI: 10.1002/admi.201800169
|View full text |Cite
|
Sign up to set email alerts
|

Local pH and Its Evolution Near Mg Alloy Surfaces Exposed to Simulated Body Fluids

Abstract: Many reports are available on degradation rates and corrosion product characterization of magnesium alloys for implant application. Typically, the data are obtained ex situ, as post factum analysis of occurred degradation processes or in bulk electrolyte that does not fully reflect concentration gradients at the interface and in the diffusion layer. Meanwhile, these local conditions are essential for tissue‐implant compatibility. Only a limited number of studies employ the techniques that visualize ongoing deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
20

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 34 publications
1
34
0
20
Order By: Relevance
“…45 The role of Ca in different solutions is varying: in NaCl it does not have an effect, whereas under more physiological conditions it can also accelerate the degradation. 46 The important role of Ca in physiological solutions was also proven by attenuated total reflectance (ATR) Fourier-transform infrared (FTIR) spectroscopy measurements, which suggested that Ca 2+ stimulates rapid precipitation of hydroxyapatite at the interface. 47 Together with P, which is always present under physiological conditions, this can induce rapid nucleation and growth of noncrystalline Ca-P precipitates, a precursor of inorganic bone matrix.…”
Section: Cell-free Situationmentioning
confidence: 99%
“…45 The role of Ca in different solutions is varying: in NaCl it does not have an effect, whereas under more physiological conditions it can also accelerate the degradation. 46 The important role of Ca in physiological solutions was also proven by attenuated total reflectance (ATR) Fourier-transform infrared (FTIR) spectroscopy measurements, which suggested that Ca 2+ stimulates rapid precipitation of hydroxyapatite at the interface. 47 Together with P, which is always present under physiological conditions, this can induce rapid nucleation and growth of noncrystalline Ca-P precipitates, a precursor of inorganic bone matrix.…”
Section: Cell-free Situationmentioning
confidence: 99%
“…The flow rate of even below 0.01 ml/min is sufficient to maintain the concentration of the solution, while it is too low to influence the corrosion process . On the other hand, even at the flow rate of as high as 1.5 ml/min, local pH, in the Nernstian diffusion layer can be clearly distinguished from the bulk values .…”
Section: Resultsmentioning
confidence: 99%
“…It seems that in the aged samples it is easy to form at the beginning of corrosion. Previous works also identified the Ca-P products in corrosion layers, [75][76][77][78] with a formation which is closely related with the presence of Ca 2+ in simulated body fluids. Following the investigation of the present alloys, it is reasonable to conclude that the formation of the present outer Ca-P layer is connected with the content of Nd inside the matrix and microstructure.…”
Section: Corrosion Proceeding Influenced By Intermetallic Microstructurementioning
confidence: 87%
“…It was reported that the calcium-phosphate layer could stabilize the surface pH value resulting in controlling Mg degradation. [78] It plays a protective role to a certain extent in reducing the deterioration from the galvanic corrosion. [70] Consequently, in the aged samples, owing to the formation of the outer Ca-P layer, the relatively compact inner corrosion layer and the dispersive distribution of nanometer precipitates inside grains, their corrosion resistance is better than the T4 sample.…”
Section: Corrosion Proceeding Influenced By Intermetallic Microstructurementioning
confidence: 99%